(untitled) (International Conference on Educational Discoveries and Humanities, 2025)
The article is devoted to the study of the interrelation of urbanization processes and crafts in the southeastern regions of Uzbekistan in the late 19th and early 20th centuries. The study analyzes the cities of Karshi, Shahrisabz, Kitab, Boysun and Denov as major centers of crafts. The article covers the main branches of crafts (textiles, cutlery), the products they produce, and the place of these products in local and foreign markets. The results show that the rapid development of crafts strengthened the economic basis of cities and increased the living standards of the city’s population.